2021
DOI: 10.1186/s41983-021-00354-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and impact of COVID-19 pandemic among neurology patients in Jordan: a cross-sectional study

Abstract: Background The impacts of the COVID-19 pandemic on health services offered to patients with non-communicable diseases, including chronic neurological illnesses, are diverse and universal. We used a self-reported questionnaire to investigate these impacts on neurology patients in Jordan and assess their knowledge and attitudes towards the pandemic. Results Most respondents had positive attitudes towards the COVID-19 pandemic, with 96% reporting they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Viral load is another important parameter to know ( Table 2 ) [ 16 ] for whether people can develop post-COVID-19 symptoms. Our results show that, at a low Ct value [ 15 , 16 , 17 , 18 , 19 , 20 ], patients have between 15 to 20 post-COVID-19 symptoms; likewise, this is reflected when analyzing patients who had an intermediate Ct [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] who presented between 6 to 11 symptoms, and, finally, there were patients with a low Ct [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] who had few or no symptoms ( Figure 3 A). Therefore, a Pearson correlation was performed between the Ct value and the number of post-COVID-19 symptoms (r = 0.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Viral load is another important parameter to know ( Table 2 ) [ 16 ] for whether people can develop post-COVID-19 symptoms. Our results show that, at a low Ct value [ 15 , 16 , 17 , 18 , 19 , 20 ], patients have between 15 to 20 post-COVID-19 symptoms; likewise, this is reflected when analyzing patients who had an intermediate Ct [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] who presented between 6 to 11 symptoms, and, finally, there were patients with a low Ct [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] who had few or no symptoms ( Figure 3 A). Therefore, a Pearson correlation was performed between the Ct value and the number of post-COVID-19 symptoms (r = 0.…”
Section: Resultsmentioning
confidence: 66%
“…Likewise, other symptoms such as anosmia and augesia can manifest after the end of the infection and can be used as prognostic markers for neuronal diseases. Other manifestations associated with this disease include the increase of migraine or cases of epilepsy; however, the evidence is still unclear because these may occur due to the infection or to the obligatory confinement [ 23 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although patients reported different experiences, a certain degree of sleep disorders was reported among almost all patients. In Jordan, Athamneh et al reported that 37.5% of patients with chronic headaches reported changes in sleeping patterns during the COVID-19 pandemic 92. Finally, the frequency of sleep problems in patients with RD was significantly higher than that of non-patients, but significantly lower than that reported in hospital workers 93…”
Section: Resultsmentioning
confidence: 97%
“…A cross-sectional study from Saudi Arabia reported that more than half of patients missed follow-up visits for their chronic condition during the pandemic [37]. Clinical experience during the global pandemic and the ensuing restrictions in Arab countries, including in the Gulf, showed delayed outpatient follow-up, medication interruptions, and decreased access to non-emergency healthcare [38,39]. Changes in pharmacological adherence due to the COVID-19 pandemic have been documented in several studies worldwide, across a wide range of chronic diseases [40][41][42].…”
Section: Plos Onementioning
confidence: 99%